Review of Factors Affecting Purchasing Power and Investment in Property: A Comparative Study between Indonesia and Neighboring Countries - Endah Kusumastuti; Thania Kusmalinda; Yudistira Nugraha; Nicko Albart (CV. Publikasi Indonesia, 2024)
The disparity in purchasing power and investment in the property sector between Indonesia and neighboring countries has attracted attention in recent years. Various aspects, both macroeconomics and socio-demographics, play a role in creating the dynamics of the property market in each country. This research explores how these factors - including inflation, interest rates, national incomes, and public policies - contribute to purchasing power parity and investment patterns in property. Through the systematic literature review (SLR) approach with 12 articles reviewed. The findings show that Indonesia faces challenges of limited access to credit, unbalanced income growth, while neighboring countries such as Singapore and Malaysia followed by Thailand and Vietnam are able to encourage stronger investment with more stable and investment-friendly economic policies. Hence, the results of this study suggest that Indonesia should adopt some best practices from neighboring countries to increase purchasing power parity and investment in the property sector in a sustainable manner.